Body, Capital, and Screens: Visual Media and the Healthy Self in the 20th Century - Bonah, Christian; Laukötter, Anja (MediaMatters, 2020)
This book began life with the inaugural conference of the international research project 'The healthy self as body capital: Individuals, market-based societies, body politics and visual media in the twentieth century Europe', held in Strasbourg from 23 to 25 February 2017. The editors would like to thank all participants for their stimulating input during this outstanding event. The presentations and discussions influenced this book in many ways. The research project and the book are funded by the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement No. 694817) and receive significant support from the University of Strasbourg, the Research Unit SAGE (UMR 7363), and the Max Planck Institute for Human Development Berlin (Center for the History of Emotions). We owe gratitude to Tricia Close Koenig, Thérèse Vicente, Lionel Boutton, Fatima Gomis, and Assia Hammali for material support with our research and Elisabeth Fuchs for translation work and subtitling (all University of Strasbourg). We would also like to thank our editor at Amsterdam University Press, Maryse Elliott, for her support in the production of the book. Moreover, we thank our contributors for their inspiring ideas and indepth research. We would like to thank the artists VALIE EXPORT for her collaboration with one of the chapters and Sascha Kürschner for working with us on the book cover. We hope that his drawing 'FEELING REAL' from his series 'PURSUIT OF HAPPINESS' provides a fitting visual prelude to an interesting read.